Pelatihan Praktek Peradilan Semu Dalam Rangka Peningkatan Kemampuan Hukum Acara Perdata - syaif, maslul (Jurnal Pengabdian Hukum Indonesia, 2020)
The implementation of moot court practice is an activity that is commonly carried out in university. However, sometimes this implementation is not carried out comprehensively because it is not handled by training of moot court in which training is provided on how the main points of procedural law are. In this service activity, a moot court practice training was held for students of the Shari'ah Faculty of Univeritas Darussalam, Gontor, Magelang Campus. Servis activity is intended to provide knowledge of the main points in civil procedural law and the preparation of case lawsuits. The results of this servis activity are first, the increase in the knowledge of the participants in the service of civil procedure law and the ability of participants in preparing case files Pelaksanaan praktek peradilan semu merupakan kegiatan yang lazim dilakukan di perguruan tinggi. Namun, terkadang pelaksanaan ini tidak dilakukan secara komprehensif karena tidak diawali dengan pelatihan praktek peradilan semu yang didalamnya diberikan pelatihan bagaiamana pokok-pokok hukum acara. Pada kegiatan pengabdian ini, dilaksanakan pelatihan praktek peradilan semu bagi Mahasiswa Fakultas Syari’ah Universitas Darussalam Gontor Kampus Magelang. Pembekalan dimaksudkan untuk memberikan pengetahuan pokok-pokok hukum acara perdata dan penyusunan berkas gugatan perkara. Hasil dari pengabdian ini adalah pertama, meningkatnya pengetahun peserta pengabdian dalam pokok-pokok hukum acara perdata dan kedua, kemampuan peserta penyusunan berkas gugatan perkara.